Perceptions and practices on substandard and falsified medicines in humans and animals in Wakiso district, Uganda: A qualitative study - David Musoke; Grace Biyinzika Lubega; Claire Brandish; Kate Russell-Hobbs; Natasha Hamilton; Jody Winter; Carol Esther Nabbanja; Filimin Niyongabo; Michael Obeng Brown; Elma Rejoice Banyen; Herbert Bush Aguma; Linda Gibson (PLoS ONE, 2025)
Background Few studies have taken a broad perspective on substandard and falsified medicines (SFMs) in community settings in Uganda. We therefore qualitatively assessed the perceptions and practices on SFMs for humans and animals in Wakiso District, Uganda. Methods This qualitative study employed 12 focus group discussions among community health workers and farmers, as well as 11 key informant interviews among health professionals, local leaders, veterinary and human drug shop operators, and Ministry of Health and Ministry of Agriculture, Animal Industry and Fisheries officials. Data was analysed thematically using NVivo (2020). Results Findings are presented under four themes: definition of SFMs; identification of SFMs; drivers of SFMs; and challenges in reporting SFMs. Although participants felt that the term SFMs was too broad to define, many explained it in relation to consequences (such as side effects, disabilities, and death), and the different methods that may be employed to identify SFMs. SFMs were said to be identified through changes in appearance such as colour, texture and packaging. However, the most reported way of identifying SFMs was based on negative effects on humans and animals after use. Customer drivers of SFMs included inadequate knowledge, lack of finances, and lack of access to licensed drug shops/ pharmacies. Supplier drivers of SFMs included limited regulation and enforcement, and the business orientation of drug shops/ pharmacies. Lack of knowledge of how to report suspected cases of SFMs, lack of proof of purchase of SFMs, fear of reporting, and lack of trust in government procedures were the challenges identified to reporting SFMs. Conclusion Several drivers of SFMs in the community were established related to individuals, sources of medicine, and regulatory frameworks. Increased awareness on SFMs, improved traceability of purchases and reporting, and better enforcement of regulations are needed to reduce the use and risks associated with SFMs to protect public health.